KONTRADIKSI IMPLEMENTASI PASAL 79A UNDANG UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN DI KOTA DENPASAR - Purna Astha, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The problem that there is a contradiction between the article 110 (1) C Undang-Undang Republik Indonesia number 28 year 2009 which is decisive that there is a contribution in the case of reimbursement cost of printing identification cards and article 79A Undang-Undang Republik Indonesia number 24 year 2013 on Residential Administration which prohibits any retribution on getting and issuing residential document. The study method employed in this study including kind of normative law study and the approach methods used are: law approach, history approach an conceptual approach. The conclusions are: considering that there a contradiction between the article 110 (1) C Undang-Undang Republik Indonesia number 28 year 2009 should not be in practiceany longer. Another conclusion is that the decree of the Majelis Madya Desa Pekraman Number : 14/12-SK/MMDP/VII/2014 in which arranged the management of incoming residents are to pay contribution when they apply for KIPS and STPPTS, is contradictory with Undang-Undang Republic Indonesia Number 24 year 2013 particularly article 79A, because the mentioned Undang-Undang is higher in position than the mentioned decree.
Keywords: council of desa pakraman; document; general services; residential; retribution,